A study of arbitrage opportunities and cost of trading on euroyen figures between Singapore Exchange (SGX) and Tokyo International Financial Futures Exchange (TIFFE). - Lee, Tien Hock. (2008)
This project explores the arbitrages opportunities and cost of trading on Euroyen futures between Singapore Exchange (SGX) and Tokyo International Financial Futures Exchange (TIFFE).